THE EFFECTIVENESS OF “I CHALLENGE GAME” IN TEACHING GRAMMAR - yuliani, yuliani (Universitas Pendidikan Mandalika, 2016)
This study was to find out the effectiveness of I challenge game in teaching grammar. This research was quasi experimental design. The population of this study was the second grade students of SMPN 2 Kediri which consisted of four classes. Two classes were chosen as the samples, those were VIII B Class as experimental group consisted of twenty six students and VIII D Class as control group consisted twenty five students. They were chosen by using simple random sampling technique. Experimental group was treated by I Challenge Game and control group was treated by Grammar Draughts Game. The instrument that was used objective test informs of multiple choices. Then, the scores were analyzed by using statistical analysis. It showed the mean score of experimental group was 67,04 while the mean score control group was 52,54 and the value of t (t test) = 1,716 was higher than (t table) = 1.677 at the significance level of 0,05% and the number of degree freedom (df) 49. It meant that alternative hypothesis (Ha) was accpeted and null hypothesis (Ho) was rejected. It could be calculated that I Challenge Game was effective in teaching grammar at the second grade students of SMPN 2 Kediri.